Actividad citoquinina y efecto de la nutrición nitrogenada en el desarrollo de raíces tuberosas de Ipomoea batatas - Pérez, D (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The relationship between tuberization induced by a period of nitrogen withdrawal and the cytokinin activity in roots, shoots and xylem exudate was investigated in water cultured plants of sweet potato (lpomoea batatas cultivar LM-24). Plants with a constant supply of nitrogen were used as control No tuberization was observed with continuous N, but discontinuous N induced tuberization 5 days after N withdrawal. The roots of plants with discontinuous N supply showed an increase in cytokinin activity, whereas the activity decreased in the continuous N treatment. In the shoot of plants with continuous N, cytokinin activity decreased, but with discontinuous N, the activity increased. In the exudate, cytokinin activity was reduced in plants with discontinuOus N during the nitrogen withdrawal, whereas the activity increased with continuous nitrogen. The increase in cytokinin activity of the shoot related to rubberization induction by the N\withdrawal may be related to an increased photosynthetic activity of the leaf in order to meet the increased assimilation requirement of the growing tuber.